Utilization and Knowledge of Teachers and Students on Computer Tech-nology: Basis for Ict Intervention Program - Madamba, Clarissa V. (Future Science / FSH-PH Publications, 2023)
The study was conducted to determine utilization and knowledge of teachers and students on Computer Technology in Zone I, Division of Zambales during the School Year 2019-2020. The sample population of the study was be limited to the use of twenty (20) teachers and two hundred seventy-five (275) students from selected secondary schools of DepEd at Zone I, Division of Zambales. The researcher framed this study based on the descriptive research design in order to gather pertinent data with regards to the presentation of the demographic profile of respondents and in the evaluation and analysis of responses made by both teacher-and student-respondents to determine both the utilization and knowledge on Computer Technology in classrooms in terms of teaching and learning, as mandated by the DepEd K-12 academic program as to provide for quality education in modern society. It also indicated that the level of significant difference on the perceptions of the respondents on utilization and knowledge of both students and teachers on the application of computer technology in classroom instruction may vary when they are grouped based on profile variables and based on categories of availability of resources, teaching styles and student knowledge in the use of computers. Furthermore, this study finds that there is no significant difference on the perceptions of the student-respondents and teacher-respondents on the perceived utilization and knowledge on the application of computer technology as to availability of resources; to teachers teaching styles; and to knowledge of students on the use of technology.